Deformation and HCF behavior of A356 aluminum alloys in torsion - Barbieri M.M.* (2019)
© 2019 IOP Publishing Ltd.In this study, monotonic, cyclic and fatigue properties of the A356 aluminum alloy were identified using torsion tests with rounded solid test specimens of the alloy in four different processing conditions. The monotonic and cyclic shear stress-strain behaviors of the alloys are described using the Ramberg-Osgood model and the materials constitutive parameters were estimated minimizing the difference between the experimental torque and the analytical value. Results of torsion fatigue tests with R = -1 were compared with rotating bending results and the load factor was evaluated. Experimental fatigue results indicated that the alloys at T6 condition showed the best behavior and the results of strontium modified alloys shown slightly lower performance. The fatigue life diagram of T6 alloys has steeper negative slope (shear fatigue strength exponent, b ≅ -0.2) than the others as cast alloys (b ≅ -0.06). The comparisons of experimental rotating bending and reverse torsion fatigue showed exponent b is dependent on the load type for the as cast alloys. For the heat-treated alloys, the variation of exponent b is minimal and its value can be considered constant.